THU0281 Use of Anti-Tumor Necrosis Factor Alpha Therapy in Patients with Inflammatory Arthritis and Concurrent History of Hepatitis B or Hepatitis C Infection: A Retrospective Analysis of 44 Patients. (10th June 2014) - Ballanti, E.; Conigliaro, P.; Chimenti, M.S.; Barbato, C.; Kroegler, B.; Di Muzio, G.; Guarino, M.D.; Triggianese, P.; Gigliucci, G.; Novelli, L.; Duca, I.; Perricone, R.
Abstract : Background: The safety of tumor necrosis factor (TNF) inhibitors in the setting of HBV and HCV infections is controversial since it has been associated with an increased risk of reactivation of HBV in Rheumatoid Arthritis (RA) and Psoriatic Arthritis (PsA). This condition can occur in both inactive and occult carriers during immunosuppressive treatment. Objectives: We report our experience of using etanercept (ETA) and adalimumab (ADA) in patients with RA and PsA and previous HBV/HCV infection. Methods: We evaluated retrospectively the medical records of 598 patients affected by inflammatory arthritis (344 RA and 254 PsA) who commenced ETA (50 mg weekly) or ADA (40 mg every other week). All patients were assessed for HBsAg, anti-HBc, anti-HBs, anti-HCV and those found positive for HBV or HCV infection were monitored with serum transaminases and HBsAg every 3 months, while HBV/HCV viral load was assessed every 6 months during the follow-up. HBV positive patients were classified as inactive HBsAg carriers or occult carriers (positive HBcAb with or without anti-HBs, undetectable serum HBV DNA and HBsAg, normal transaminases levels). Data are expressed as mean ± standard deviation. Statistic was performed using Fisher's exact test. Results: We identified 32 RA patients (M/F 2/30, age 57.6±9.1 years, disease duration 6.9±5.6 years, DAS28 5.9±1.1, anti-TNF duration 27.1±23.7 months, 22 treated with concomitant DMARDs) and 12 PsA patients (M/F 8/4, age 63.4±7.9 years, disease duration 15.3±10.4 years, DAS28 5.6±1.9, anti-TNF duration 25.3±23.9 months, 8 treated with concomitant DMARDs) positive for anti-HBc and/or HBsAg or anti-HCV. In RA there were 25 HBV occult carriers (7.3%, 24 positive for anti-HBc and anti-HBs, 1 positive for anti-HBc only), 1 HBV inactive carrier (0.2%), and 6 anti-HCV positive patients (1.7%). In PsA there were 10 HBV occult carriers (3.9%, all positive for anti-HBc and anti-HBs) and 2 anti-HCV positive patients (0.7%). There was not difference in the prevalence of HBV/HCV infection between RA and PsA patients. Three RA patients and one PsA patient received prophylactic treatment with Lamivudine (100 mg/die). During the follow-up we didn't detect HBsAg positivization and HBV DNA/HCV RNA were undetectable in all patients. 11 patients (7 RA patients and 4 PsA patients) showed an increase of transaminases (Table 1). There was not significant difference in the percentage of transaminases' increase between RA and PsA and between ETA and ADA groups. This increase was associated with the concomitant use of DMARDs, NSAID, isoniazid prophylaxis or alcohol abuse and was reverted by treatment adjustment and alcohol restriction. However, three patients had to discontinue anti-TNF for persistent increase of transaminases. Conclusions: We didn't observe HBV/HCV reactivation in 44 patients with inflammatory arthritis treated with anti-TNF. Anti-TNF therapy appeared to be safe in RA and PsA patients with previous HBV or HCV infection, monitoring remains necessary especially in patients treated with concomitant hepatotoxic drugs. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3170